2017
DOI: 10.1111/nph.14593
|View full text |Cite
|
Sign up to set email alerts
|

Co‐introduction vs ecological fitting as pathways to the establishment of effective mutualisms during biological invasions

Abstract: Contents 1354I.1354II.1355III.1357IV.1357V.13591359References1359 Summary Interactions between non‐native plants and their mutualists are often disrupted upon introduction to new environments. Using legume–rhizobium mutualistic interactions as an example, we discuss two pathways that can influence symbiotic associations in such situations: co‐introduction of coevolved rhizobia; and utilization of, and adaptation to, resident rhizobia, hereafter referred to as ‘ecological fitting’. Co‐introduction and ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…Such HGT between non‐native Australian and native resident bradyrhizobia has previously been reported in Portugal (Rodríguez‐Echeverría, ). Horizontal gene transfer may translate into more severe acacia impacts if, for example, it leads to reduced chemoattraction of rhizobia by native legumes and thus lowered symbiotic effectiveness (Le Roux et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such HGT between non‐native Australian and native resident bradyrhizobia has previously been reported in Portugal (Rodríguez‐Echeverría, ). Horizontal gene transfer may translate into more severe acacia impacts if, for example, it leads to reduced chemoattraction of rhizobia by native legumes and thus lowered symbiotic effectiveness (Le Roux et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that when introduced species are cointroduced with their mutualists they may become more invasive and have greater ecological impact than those that establish mutualisms by ecological fitting (Le Roux et al, ). Novel associations may not be optimal and thus limit the performance of non‐native plants.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stability of the plant-legume mutualism was also explained by this cost/reward process. Plants that are selected to supply preferentially more resources to nodules that are fixing more N 2 can be crucial to the establishment of effective legumerhizobium mutualisms during biological invasions (Le Roux et al 2017).…”
Section: Trait-mediated Interactions and Adaptive Network: Mutualistmentioning
confidence: 99%